Hemoglobin-based oxygen carriers, oxidative stress and myocardial infarction - Estep, Timothy N. (Frontiers in Physiology, 2025)
IntroductionDevelopment of hemoglobin-based oxygen carriers (HBOCs) for use as temporary blood replacement solutions and treatment of hemorrhagic shock has been hindered because of evidence HBOC infusion increases the risk of myocardial infarction (MI).MethodsTo gain insight into potential toxicity mechanisms, MI incidence from later stage clinical testing of five HBOCs was compared to pharmacokinetic and biochemical parameters to identify correlations suggestive of cause-and-effect hypotheses.ResultsThere are positive correlations between MI incidence and HBOC dose, size, intravascular half-life and area under the plasma concentration versus time curve (AUC). Furthermore, MI incidence is positively correlated with initial rates of HBOC autoxidation, oxidation by nitric oxide, and AUCs estimated for these HBOC oxidation products.ConclusionsThese observations imply that increased MI risk after HBOC infusion is due to intravascular reactions which exacerbate oxidative stress.